Peripheral PDLIM5 expression in bipolar disorder and the effect of olanzapine administration - Zain, M.A.; Jahan, S.N.; Reynolds, G.P.; Zainal, N.Z.; Kanagasundram, S.; Mohamed, Z. (2012)
Background: One of the genes suggested to play an important role in the pathophysiology of bipolar disorder (BPD) is PDLIM5, which encodes LIM domain protein. Our main objective was to examine the effect of olanzapine treatment on PDLIM5 mRNA expression in the peripheral blood leukocytes of BPD patients.Methods: We measured the expression of PDLIM5 mRNA from 16 patients with BPD Type I after 0, 4, and 8 weeks of treatment with olanzapine using quantitative real-time PCR. The Young Mania Rating Scale was used to evaluate the severity of manic symptoms in BPD patients. We also compared PDLIM5 mRNA expression in treatment-naïve BPD patients with that in healthy control subjects.Results: No significant difference was found in PDLIM5 mRNA expression between patients before olanzapine treatment and following 4 and 8 weeks of treatment (p>0.05). Although we observed a significant reduction in the severity of manic symptoms in all BPD patients (p<0.05), the effectiveness of the medication did not significantly correlate with the expression of PDLIM5 mRNA (p>0.05). Interestingly, PDLIM5 mRNA expression differed significantly between treatment-naïve BPD patients and healthy control subjects (p=0.002).Conclusion: PDLIM5 mRNA expression did not appear to be a reflection of the efficacy of olanzapine in reducing the manic symptoms of BPD. The significant difference in expression of PDLIM5 mRNA in the peripheral blood leukocytes of treatment-naïve BPD patients versus that of healthy control subjects, however, suggests that it may be a good biological marker for BPD. © 2012 Zain et al.; licensee BioMed Central Ltd.